Real-time WIP Shelf life Tracking with Barcode Technology for Defects Reduction - Rusman, Oktalia; Sriwarna, Iphov Kumala; Prambudia, Yudha (MSD Institute, 2024)
In manufacturing systems, the short shelf life of WIP (Work-in-process), categorized as a fast-moving product, can be a source of potential defects. PT XYZ is a cocoa industry located in Bandung. Manual labeling of product information in the wafer production line at PT XYZ failed to meet secure tracking and tracing requirements, resulting in increased defects due to inaccuracies in monitoring and quality control. To solve this problem, the author used the Gemba Kaizen approach as a tool companies use for continuous improvement achieved through small, low-cost steps. Our main idea is to introduce a new approach that utilizes alternative technologies by developing real-time applications to track WIP movement information in production. This barcode technology uses low-cost technology and has proven effective in helping production supervisors speed up decision-making of WIP management and minimize the risk of process failure in production that causes an increase in the number of defects. The results showed that the real-time system can reduce the number of defects from 2.6% to 1.6%. This can optimize overall inventory management and provide valuable insights for manufacturing companies looking to improve their operational efficiency through low-cost technology and real-time monitoring.